The association between physical activity and fear of falling among community-dwelling older women in China: the mediating role of physical fitness - Wu, Shuang; Li, Guangkai; Shi, Beibei; Ge, Hongli; He, Qiang (Frontiers in Public Health, 2023)
Background: This study aimed to explore the association between physical activity (PA) and Fear of falling (FOF) and to determine whether this relationship was mediated by physical fitness (PF) in community-dwelling older women.For this cross-sectional study, a total of 1108 older women were recruited.-to-vigorous physical activity (MVPA) and light physical activity (LPA) was objectively measured by accelerometers. Physical fitness indicators including body mass index (BMI), forced vital capacity, choice reaction time, grip strength, sit and reach, five times sit-to-stand were measured. FOF was evaluated by the Chinese version of the activity specific balance self-confidence scale. A stepwise linear regression model analysis was used for mediation analysis and bootstrap analysis was used to verify the mediation effects. Result: The Pearson correlation coefficients results suggested that MVPA was significantly and negatively correlated with FOF while LPA was not correlated with FOF. Logistic regression analysis suggested that a significant association between MVPA , BMI, force vital capacity, choice reaction time, sit and reach, grip strength, five times sit-to-stand and FOF. The mediation analysis showed a negative relationship between MVPA and FOF. BMI completely mediated the relationship between MVPA and FOF while sit and reach, five times sit-to-stand, force vital capacity partially mediated the relationship between MVPA and FOF. Conclusion: Accumulation of more daily MVPA was associated with reducing odds of FOF in community-dwelling older women. PF indicators fully or partially mediates the relationship between MVPA and FOF. Therefore, more intervention efforts should focus on the promotion of MVPA to improve PF and thus, to reduce FOF among older women.